The Contemporary Situation and Preferences of the Ukrainian Rural Family - Vasylchenko, Alona; Vaishar, Antonin (Eastern European Countryside, 2024)
The purpose of this paper is to determine the family situation and family pref- erences in rural parts of the Ukraine. This study investigates social integration of people in various types of municipalities and size characteristics of families. The results were compared with Ukrainian urban families and Czech rural and urban families. Besides the statistical data, results of a questionnaire survey were organised by means of social networks were used. The results suggested that relations between people and their community life and their social integration are influenced by the cultural context, historical aspects and the economic level. The differences between the contemporary Czech and Ukrainian rural families can be observed in different pathways and in a different part of the job market.